Implementasi Kualitas Produk PT. Nina Venus Indonusa 2 Sukabumi - Shera Wulan Ruswandi; R. Deni Muhammad Danial; Nor Norisanti (IPM2KPE, 2019)
The purpose of this research is to find out what factors most influence the quality of products at PT. Nina Venus Indonusa 2 Sukabumi. The method used in this research is qualitative and descriptive research methods with data collection techniques in the form of observation, interviews and documentation. Data analysis methods used are data reduction and data presentation and conclusions or verification. The results of this study are wig products in accordance with established standards because PT. Nina Venus Indonusa 2 Sukabumi Maintain good quality of the products used by sending samples of raw materials before processing. Conclusions, Product Quality at PT. Nina Venus Indonusa 2 Sukabumi is very important to help increase the value of the company by paying attention to the quality of products marketed so that consumers are satisfied with the results of products made from wigs that have been produced at PT. Nina Venus Indonusa 2, because PT. Nina Venus Indonusa 2 Sukabumi observed how the trends or needs that are needed in the market Keywords: Product quality